The Dynamics of the Opposition and Coalition Parties within the Indonesian Pancasila Democratic System - Titi Mahira A’dawiyah; Anang Dony Irawan (Universitas Muhammadiyah Yogyakarta, 2023)
Pancasila democracy places the people at the center, focusing on the ideology of democracy and Pancasila as the state's guiding principle. In the current era of political openness and transparency, various dynamics have emerged, including changes in the democratic system over time in Indonesia and conflicts experienced by political parties, ranging from opposition as government watchdogs to coalitions as policy-makers. These dynamics have given rise to numerous theories regarding the function of state institutions. One of the most prominent theories is Montesquieu's trias politica, which divides power into the Executive, Legislative, and Judiciary, serving as a balancing mechanism for democracy and the dynamics within the Indonesia. This study utilizes normative legal materials, namely books, legal journals, and online sources, to examine the background of the problem. Within this research, it was discovered that the dynamics of democracy in Indonesia are influenced by historical factors deeply ingrained in its fabric. Furthermore, the state ideology has undergone several transformations, starting from the shift from guided democracy to Pancasila and subsequently the reformation era, ultimately culminating in the present. There have been numerous disputes in the pursuit of becoming a sovereign democratic nation in accordance with the 1945 Constitution and Pancasila.